AB0329 The method of evaluation of cardiorespiratory system neurovegetative regulation in rheumatologic patients. (12th June 2018) - Lebedeva, A.; Marchenko, V.; Mozhaev, I.
Abstract : Objectives: To study the characteristics of cardiorespiratory system (CRS) neurovegetative regulation disorders and to define the correlation with disease activity. Methods: 40 rheumatoid arthritis (RA) patients (14 m:30 f; median age 45±2, 32), 18 ankylosing spondylitis (AS) patients (13 m:5 f; m.a. 39, 6±2, 44), 17 osteoporosis (OP) patients (3 m:14 f; m.a. 55.5±1, 47), 50 healthy persons (HP, 25 m:25 f; m.a. 23, 8±0, 84) were studied. The diagnosis' of RA, AS, OP were established by the current diagnostic and classification criteria. The cardiorespiratory system neurovegetative regulation was studied with the use of Spiroarteriocardiorhithmograph, that was able to synchronously analyse the variability of heart rate (HR), respiration (R), systolic (S) and diastolic (D) arterial pressure, respiratory phase structure, baroreceptor sensitivity and some other cariohemodynamics parameters. Following parameters were calculated: spectrum of fluctuations total power (TP), the activity of suprasegmental (VLF), sympathetic (LF), parasympathetic (HF), cortical (IC) and subcortical (SNCA) contours and sympatho-vagus balance parameters (LF/Hf) in regulation HR, R, S, D, baroreceptory sensivity (BR), inhale (Ti) and exhale (Te) time (V. Marchenko, 2004). Results: Different severity dysregulation of CRS at all levels is typical for the AS patients, which expresses in decrease of the variability of the basic contours of regulation of heart rate, respiration, systolic and diastolic blood pressure with a shift of sympatho-vagal balance in favour of parasympathicotonia, reduction baroreceptor sensitivity. The heterogeneity of the analysed groups according to the parameter LF/HFHR is shown. The ratio of patients with parasympathotony, normotony, sympathotony in groups made up, respectively, in HP (34:48:18), RA (23:54:23), AS (55:28:17), OP (29:53:18). It is established that a significant number of AS patients had parasympathetic type of regulation, and the rest of the groups were dominated by patients with normotonic type of regulation. It is shown that in groups of patients neurovegetative regulation system was more stringent, as evidenced by the increase in their number of reliable correlations compared with the group of healthy individuals. The features of disregulation in each analysed group were established, the nature of which requires further analysis. Significant correlations (τ >±0, 45; p=0, 029) between the parameters of the neurovegetative regulation of cardiorespiratory system on the one hand and the clinical and laboratory parameters of inflammatory activity (in the first place, DAS28, CRP, ESR) on the other hand in patients with RA; with parameters BASDAI, the activity of the inflammatory process (ESR, CRP) in patients with AS; densitometric parameters in patients with OP were identified. The close connexion between vascular component and the activity of the inflammatory process is shown, which may be a manifestation of endothelial dysfunction. Conclusions: Thus, the method of variability of cardiorespiratory allows to detect the neurovegetative dysregulation of the cardiorespiratory system in rheumatologic patients and can be recommended for the evaluation of the system of regulation in general, the possible role of its disorders in the pathogenesis of clinical manifestations of diseases, and assessing the dynamics of regulatory processes in the treatment of patients. Disclosure of Interest: None declared